Optimizing Transition of Care Through the Facilitation of a Pharmacist-Managed Deep Vein Thrombosis Treatment Program. (August 2013) - Davis, Kyle A.; Miyares, Marta A.; Price-Goodnow, Venessa S.
A pharmacist-managed deep vein thrombosis (DVT) treatment program was put into operation at Jackson Memorial Hospital in Miami, Florida to provide appropriate transition of care to the outpatient setting for patients diagnosed with DVT. A postgraduate year 1 pharmacy practice resident partnered with a clinical pharmacist to establish and implement the DVT pilot program in the emergency department (ED). Once contacted, the pharmacy resident or the clinical pharmacist communicated with the ED physician and made recommendations regarding appropriate anticoagulation. The pharmacist met with the patient to obtain informed consent and provide counseling regarding the anticoagulants. A timely outpatient appointment at the pharmacy-managed warfarin clinic was arranged for the patient and contact information was exchanged between the patient and the pharmacist. On average, patients enrolled in the DVT program from the ED were released 18.29 hours (±7.06) following the time of arrival. Following release from the hospital, 91% of patients attended their outpatient follow-up appointment at the warfarin clinic. Since the initiation of the DVT program, 1 patient experienced a recurrent DVT and major bleed during their treatment course. Due to successful implementation of this pharmacist-managed DVT program in the ED, the services were subsequently extended to inpatients with DVT.